Sistem Informasi Laboratorium Dengan Metode Joint Application Design (JAD) Berbasis Website (Kasus: Laboratorium Artificial Intelligence Universitas Nasional) - Aldisa, Rima Tamara; Wahyuddin, Mohammad Iwan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Data processing is a routine thing needed by organizations that must be developed properly in order to produce accurate information. Therefore, it is necessary to have a system to perform this task quickly and precisely, namely a computer with superior data processing in processing, storing, presenting, and analyzing so that the results are accurate and fast. Artificial Intelligence Computer Laboratory of the Faculty of Communication and Information Technology at the National University designed an Information System using the Joint Application Design (JAD) method as the first step or system design flow as a means to perform manual administrators or special systems in making reports related to data processing and inventory. The results of the design or system will be made based on the Website.